Blockchain orchestrated secure medical data transmission via attribute-based encryption - Mohan, M. Smitha; Sujihelen, L. (Ain Shams Engineering Journal, 2025)
Electronic health records (EHRs) are crucial digital documents that contain patient medical information. Medical data sharing faces critical challenges, including a lack of robust security mechanisms, inefficiencies in sharing data, and significant vulnerabilities in maintaining privacy for EHRs. To overcome these challenges, a novel Blockchain ORchestrated Encryption for medical data (BORE-MED) has been suggested to enhance the security for managing sensitive medical information (SMI) of EHR in the healthcare sector. The proposed methodology employs the Attribute-Based Encryption (ABE) algorithm to encrypt the EHR data for enhancing data privacy. The Mirrored Byzantine Fault Tolerance (Mir-BFT) consensus algorithm is utilized securely storing and sharing EHRs. The proposed system has been evaluated using a Python simulator. The security of the suggested BORE-MED framework is 5.63%, 7.57%, and 8.9% higher than the existing BSC, BLE, and PPAC methods respectively. These findings reveal that the developed framework presents a secure data transmission in healthcare sector.